Deformation of the Geocell Flexible Reinforced Retaining Wall under Earthquake - Yalin Zhu; Kun Tan; Yin Hong; Ting Tan; Manrong Song; Yixian Wang (Advances in Civil Engineering)
As a new type of reinforced material, geocells are widely used in flexible reinforced retaining wall projects, and a lot of practical experience shows that the geocell retaining wall has a great effect on earthquake resistance, but theoretical research lags behind engineering practice, and the deformation and failure mechanism under earthquake need to be further studied. In this paper, we use the FLAC3D nonlinear, finite-difference method to study the failure mechanism of geocell-reinforced retaining walls under earthquake, to analyze the advantages of the geocell retaining wall in controlling deformation compared with the unreinforced retaining wall and geogrid-reinforced retaining wall, and we try to study the deformation of the reinforced wall by changing the length of the geocell and reinforcement spacing of the geocell. Research indicates the horizontal displacement of the wall edge of the reinforced retaining wall under the earthquake is slightly smaller than that of the center of the wall and the back of the wall. The geocell can effectively reduce the horizontal displacement of the retaining wall, and the effect is better than the geogrid. Increasing the length of the geocell and reducing the spacing of the geocell can effectively reduce the horizontal displacement of the retaining wall, and the effect of displacement controlling at the top of the wall is better than in other positions.